Analyzing Students’ Collaborative Skills Through Self-Assessment in Renewable Energy Project - Khairunnisah Khairunnisah; Lina Aviyanti; Asep Suryanto; Bolushova Fatima (Universitas Lambung Mangkurat, 2026)
This study investigated high school students’ collaborative skills through self-assessment in a renewable energy project-based learning (PBL) endeavor. A descriptive quantitative approach was applied, involving 75 students engaged in a project on renewable energy. Data were collected using the Collaboration Self-Assessment Tool (CSAT), which consists of 11 Likert-scale items covering interpersonal and intrapersonal domains, along with three open-ended reflection questions. The data were analyzed using the Rasch model with Winstep version 5.10.1.0 to examine the instrument’s quality and students’ responses. The findings show that the CSAT meets key measurement criteria, including acceptable unidimensionality (39.3% variance explained) and good reliability (person reliability = 0.76, item reliability = 0.90, Cronbach’s alpha = 0.81). Most items functioned well, although the Wright Map indicates that the instrument was relatively easy for the students. In terms of performance, students scored higher in intrapersonal skills (82.9%) than in interpersonal skills (77.5%). Most students were categorized at the established level of collaboration, while smaller proportions were at developing and emerging levels. Responses to open-ended questions further suggest that students were able to reflect on their roles and identify ways to improve their collaboration. Overall, CSAT can be used as a practical tool to assess collaborative skills in PBL settings. The results also point to the need for strengthening interpersonal aspects of collaboration and developing more challenging items for future use.